Sharing world leadership? : (American Enterprise Institute for Public Policy Research, 1989)
The special relationship forged after World War II between Japan and the United States has served both nations well. Japan especially has been remarkably successful in its economic growth and development. By relinquishing its former military and imperial ambitions and allowing key U. S. military bases on its soil, Japan has been able to pursue its economic miracle under the aegis of U. S. security.